2017
DOI: 10.1097/dss.0000000000001113
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features and Treatment of Dermatofibrosarcoma Protuberans Affecting the Vulva: A Literature Review

Abstract: This literature review comprehensively reviews and describes the clinical presentation of vulvar DFSP and the treatment options for this rare vulvar neoplasm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…Some cases of breast DFSP with negative margin reported the use of postoperative radiotherapy, but no long-term follow-up data included. It is reported that most DFSP have the translocation t(17; 22) (q22; q13), resulting in the COL1A1-PDGF β fusion gene, which provides a biological basis for treatment with tyrosine kinase inhibitors, such as imatinib [ 52 ]. In the advanced or metastatic group, imatinib therapy is warranted if a unique translocation is confirmed [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some cases of breast DFSP with negative margin reported the use of postoperative radiotherapy, but no long-term follow-up data included. It is reported that most DFSP have the translocation t(17; 22) (q22; q13), resulting in the COL1A1-PDGF β fusion gene, which provides a biological basis for treatment with tyrosine kinase inhibitors, such as imatinib [ 52 ]. In the advanced or metastatic group, imatinib therapy is warranted if a unique translocation is confirmed [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…DFSP is rarely described in the vulva 36,37 . Nguyen et al published the largest series of cases of vulvar DFSP, 33 cases, arising slowly as tender asymptomatic masses on labia majora 36 .…”
Section: Discussionmentioning
confidence: 99%
“…DFSP is rarely described in the vulva 36,37 . Nguyen et al published the largest series of cases of vulvar DFSP, 33 cases, arising slowly as tender asymptomatic masses on labia majora 36 . This soft tissue tumor is described overall as a superficial low‐grade sarcoma of intermediate malignancy that typically arises in the trunk and proximal extremities 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Lesions presented with erythema, hyperpigmentation, ulceration, or even of orange peel skin appearance. Patients reported slow to minimal change in size (ranging from 3 months to 10 years) [7]. As with all solid tumors, clinical suspicion is confirmed by biopsy.…”
Section: Discussionmentioning
confidence: 99%